Cytostatic and Cytotoxic Properties of Amphinase: A Novel Cytotoxic Ribonuclease from Rana pipiens Oocytes - Ardelt, Barbara (2007)
Onconase (Onc) is a novel amphibian cytotoxic ribonuclease with antitumor activity and is currently in a confirmatory phase III clinical trial for the treatment of malignant mesothelioma. It was recently reported that Rana pipiens oocytes contain still another ribonuclease, named Amphinase (Amph). Amph shows 38-40% amino acid sequence identity with onconase, presents as four variants varying between themselves from 87-99% in amino acid sequence identity and has a molecular mass ∼13,000. In the present study we describe the effects of Amph on growth of several tumor cell lines. All four variants demonstrated cytostatic and cytotoxic activity against human promyelocytic HL-60-, Jurkat T-cell- and U-937 monocytic leukemia cells. The pattern of Amph activity to certain extent resembled that of Onc. Thus, cell proliferation was suppressed at 0.5-10.0 µg/ml (38-770 nM) Amph concentration with distinct accumulation of cells in G(1) phase of the cell cycle. In addition, the cells were undergoing apoptosis, which manifested by DNA fragmentation (presence of “sub-G1” cells, TUNEL-positivity), caspases and serine proteases activation as well as activation of transglutaminase. The cytotostatic and cytotoxic effects of Amph required its ribonuclease activity: the enzymatically inactive Amph-2 having histidine at the active site alkylated was ineffective. The effectiveness and cell cycle specificity was generally similar for all four Amph variants and at the equimolar concentrations was somewhat more pronounced than that of Onc. The observed cytostatic and cytotoxic activity of Amph against tumor cell lines suggests that similar to Onc this cytotoxic ribonuclease may have antitumor activity and find an application in clinical oncology.